2023
DOI: 10.3390/toxins15090582
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Risks of Diffusion of Cyanobacteria Toxins in Rivers, Lakes, and Potable Water

Amin Mahmood Thawabteh,
Hani A Naseef,
Donia Karaman
et al.

Abstract: Blue-green algae, or cyanobacteria, may be prevalent in our rivers and tap water. These minuscule bacteria can grow swiftly and form blooms in warm, nutrient-rich water. Toxins produced by cyanobacteria can pollute rivers and streams and harm the liver and nervous system in humans. This review highlights the properties of 25 toxin types produced by 12 different cyanobacteria genera. The review also covered strategies for reducing and controlling cyanobacteria issues. These include using physical or chemical tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 347 publications
0
6
0
Order By: Relevance
“…Tap water and washing machines were sampled from 22 households in Shanghai, and the microorganisms in the washing machine environment were analyzed. Although it is reported that one of the most significant concerns with tap water is the presence of harmful microorganisms, such as bacteria, viruses, and parasites [ 36 , 37 ], quantitative analysis revealed a significantly higher number of microorganisms in the water samples from washing machines compared to tap water. This indicates that tap water is not the main source of microbial contamination in washing machines.…”
Section: Discussionmentioning
confidence: 99%
“…Tap water and washing machines were sampled from 22 households in Shanghai, and the microorganisms in the washing machine environment were analyzed. Although it is reported that one of the most significant concerns with tap water is the presence of harmful microorganisms, such as bacteria, viruses, and parasites [ 36 , 37 ], quantitative analysis revealed a significantly higher number of microorganisms in the water samples from washing machines compared to tap water. This indicates that tap water is not the main source of microbial contamination in washing machines.…”
Section: Discussionmentioning
confidence: 99%
“…This includes evaluating the advantages and disadvantages of using phytoplankton, zooplankton, benthic macroinvertebrates, microorganisms, aquatic plants, fish, and allelochemicals, integrating findings from relevant studies. The exploration of innovative technologies, such as remote sensing, DNA sequencing, and machine learning, for early detection and prevention of HABs is discussed, highlighting their potential for real-time monitoring and prediction across various types of aquatic infrastructure [170][171][172][173][174][175]. This review of biological methods for controlling HABs underscores the importance of assessing potential benefits and impacts on native communities and potential toxicity within different infrastructure settings.…”
Section: Passive Strategies For Managing Harmful Algal Blooms (Habs) ...mentioning
confidence: 99%
“…Various strategies, including chemical, biological, and hydrodynamic approaches, are utilized in the management of cyanobacteria blooms (Huh & Ahn, 2017; Mitrovic et al, 2011; Senavirathna et al, 2021). However, chemical approaches may introduce new pollutants; biological methods carry risks of species invasion and difficulties in long‐term monitoring (Thawabteh et al, 2023). Consequently, from an environmental and ecological standpoint, hydrodynamic methods emerge as a more sustainable option.…”
Section: Introductionmentioning
confidence: 99%